Pengaruh Produktivitas Kerja Karyawan Sebelum dan Sesudah Pelatihan pada DPD Gerindra Jawa Barat - Elihu, Elihu; Apriadi, Deri (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to analyze the effect of training programs on employee work productivity at DPD Gerindra West Java. This study is quantitative research with a comparative approach that compares work productivity levels before and after the implementation of training programs. The research sample consisted of 30 respondents who are employees at DPD Gerindra West Java. Data collection was conducted through questionnaires that had been tested for validity and reliability, as well as direct observation. Data analysis used paired sample t-test to see the significance of productivity differences before and after training. The results showed a significant increase in work productivity after the implementation of the training program, with the average productivity value increasing from 65.7 to 82.3 (p<0.05). The indicators that experienced the highest increase were the ability to complete tasks on time (27.5%) and quality of work results (24.8%). This research provides important implications for the management of political organizations in developing effective training programs to improve human resource performance. These findings can also be the basis for continuous evaluation of the effectiveness of training programs implemented in political organizations.